Russian Federation : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2009)
This report focuses on the observance of standards and codes for the Financial Action Task Force on Money Laundering (FATF-40), recommendations for anti-money laundering (AML), and nine special recommendations combating the financing of terrorism (CFT) for the Russian Federation. Laundered money is often invested in real estate or security instruments. The report reveals that the Russian authorities are well aware of the money laundering (ML) and terrorist financing (TF) schemes used in Russia. Many ML schemes also involve the misuse of (foreign) legal entities and financial institutions.